2023
DOI: 10.3390/bs13121000
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Math Skills, Motor Skills, Physical Activity, and Obesity in Typically Developing Preschool Children

Pedro Flores,
Eduarda Coelho,
Isabel Mourão-Carvalhal
et al.

Abstract: There is evidence of a relationship between motor and cognitive development. The literature has shown that of all the motor skills, fine motor skills are those that contribute most to mathematical performance in preschool children. As this is a sensitive period in the development of motor skills, low levels of physical activity in this period can compromise their development and contribute to weight gain and obesity. The aim of this study was therefore to analyze the relationship between mathematical and motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 210 publications
2
9
0
Order By: Relevance
“…Compared with prior studies, our relatively smaller sample size may also explain the non-significant results reported in the current study. However, the number of participants in our study was comparable to corresponding research in this field [9,11,47,48]. Body fat content was measured indirectly by measuring skinfold thickness, and although Slaughter's equation has fairly high validity with DEXA for calculating BF% in children, DEXA is still considered the gold standard in body composition assessment [49].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Compared with prior studies, our relatively smaller sample size may also explain the non-significant results reported in the current study. However, the number of participants in our study was comparable to corresponding research in this field [9,11,47,48]. Body fat content was measured indirectly by measuring skinfold thickness, and although Slaughter's equation has fairly high validity with DEXA for calculating BF% in children, DEXA is still considered the gold standard in body composition assessment [49].…”
Section: Discussionsupporting
confidence: 56%
“…Martin et al [8] observed that a higher body mass index (BMI) in 3-year-old boys was associated with worse visuospatial skills, yet not with expressive language skills or reasoning skills at 5 years. Flores et al [11] reported that obesity was not associated with arithmetical performance among 3-6-year-old children. In addition, previous studies disagree on whether higher regional or whole-body fat content predicts worse cognitive performance [7,12,13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Spatial reasoning is an integral part of everyday life, and having good spatial skills strongly predicts children's future performance in various subjects. In this sense, the books "Exploring the 3-D World: Developing Spatial and Math Skills for Young Children" (Hansel, 2021) and "Blocks and Beyond: Strengthening Early Math and Science In this sense, considering the direct influence of GMS on VMI skills (Flores et al, 2023b) and that numerous programs to develop VMI skills include working on spatial skills through the manipulation of objects in a classroom context, the aim of this study was to present a set of activities to develop spatial skills, using playful activities with a strong involvement of GMS, which could be carried out in a classroom context, at the playground or at home.…”
Section: Intervention Programs To Develop Vmimentioning
confidence: 99%
“…There are studies to suggest inverse relationships between body fatness and cognitive abilities in early childhood [1][2][3], while other investigations have not found associations between body fatness and cognitive abilities [2,4,5]. For example, Haapala et al [3] found a negative relationship between body fat percentage (BF%) with reading fluency and reading comprehension in 6-8-year-old boys.…”
Section: Introductionmentioning
confidence: 99%